Implementasi Algoritma AES Sebagai Kriptografi Simetris Untuk Proses Enkripsi Dan Dekripsi Data - Rio Adian Juandana; Atika Prawiti Harahap; Zuraidah Putri Br. Hutabarat; Anggi Dwi Mentari Matondang; Ulfia Maulida; Muhammad Athaya Nasywa (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
Cryptography is one method used to transform data into a form that cannot be read without a special key. One of the most widely used symmetric cryptographic algorithms is the Advanced Encryption Standard (AES). AES was developed to replace DES with advantages in its complex yet efficient algorithm structure. This study aims to examine the structure and implementation of the AES algorithm in the process of data encryption and decryption. The method used is literature review and simple implementation using Python programming language. The results show that encryption and decryption processes can be performed consistently and accurately using a symmetric key, in accordance with AES principles.